THE PRICE OF POLITICS: INSTITUTIONAL REENGINEERING AS ANTI-CORRUPTION DISMANTLEMENT UNDER JOKOWI’S ADMINISTRATION (2014-2024) - Agie Nugroho Soegiono; Ayu Puspita Ningrum; Muhammad Dzulfikar Al Ghofiqi; Nurul Jamila Hariani; Eko Supeno (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
This study maps corruption trends in Indonesia during President Joko Widodo’s administration (2014–2024) using a systematic mixed studies review (SMSR) with a Parallel-results Convergent Synthesis Design. By integrating a systematic literature review (SLR) and focus group discussions (FGDs), this research uncovers the entrenched structural, political, and bureaucratic mechanisms that sustain corrupt practices. Corruption in Indonesia is not merely a legal violation but a systemic issue deeply embedded in governance structures, oligarchic influence, and patronage politics. Key drivers include weak democratic institutions, ineffective law enforcement, high political costs, and transactional politics in public office appointments. The study highlights how corruption persisted under Jokowi’s administration through the 2019 revision of the KPK Law, regulatory capture by political elites, and law enforcement intervention in procurement processes. Additionally, media and civil society organizations, which should serve as independent watchdogs, have often been co-opted by political and economic interests, undermining their role in anti-corruption efforts. The findings emphasize that eradicating corruption requires comprehensive institutional reforms, integrity-driven leadership, and fundamental cultural shifts toward transparency and accountability. A multidimensional strategy engaging political institutions, civil society, and oversight agencies is essential to breaking entrenched corruption networks. This study contributes to the broader discourse on governance by offering a framework for future research and policy reforms aimed at strengthening anti-corruption mechanisms in Indonesia.